Efficacy and safety of different interventions to accelerate maxillary canine retraction following premolar extraction: A systematic review and network meta‐analysis. (4th August 2020) - MacDonald, Laura; Zanjir, Maryam; Laghapour Lighvan, Nima; da Costa, Bruno R.; Suri, Sunjay; Azarpazhooh, Amir
Abstract: Decreasing orthodontic treatment duration is at the forefront of innovation for clinical orthodontics. This network meta‐analysis aimed to determine the relative efficacy and safety of treatments for accelerated orthodontic tooth movement (OTM) in patients undergoing extraction of maxillary first premolars followed by canine retraction in any orthodontic setting. MEDLINE, EMBASE, Cochrane CENTRAL, CINAHL and SCOPUS were searched (from inception to 20 April 2020). Study selection and data extraction were performed in duplicate. Eligible randomized controlled trials (RCTs) were meta‐analysed to estimate the rate of tooth movement, 95% credible interval and surface under the cumulative ranking curve (SUCRA) in the first 3 months following the application of the adjunctive accelerative method. Eligible RCTs were assessed by Cochrane risk of bias tool, and quality of evidence was assessed by GRADE approach, obtained from CINeMA web application. Interventions were ranked for efficacy and reviewed for safety. Nineteen studies pertaining to eight interventions, with data from 415 patients were included. Quality of evidence was very low to moderate. Very low‐to low‐quality evidence suggests that corticotomy is an efficacious and safe adjunctive treatment to accelerate OTM in comparison with conventional treatment in the first 2 months of treatment. Low‐quality evidence suggests that piezocision and micro‐osteoperforations (MOP) are efficacious and safe adjunctive treatments only in the first month of treatment. Frequent MOP in conjunction with low‐level laser therapy appeared to be an efficacious and safe adjunctive treatment only in the first month following its initial application but not thereafter.